Contraceptive practices and awareness about emergency contraception among women attending a tertiary care hospital of Delhi, India - Renjhen, Prachi; Kumar, Vikas; Rathi, Akanksha; Loukya, Attuluri (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Emergency contraceptive pills (ECs) are a safe female-controlled method of post-coital contraception; however, the knowledge about them is low among general population. Methods: This cross-sectional study was done among the adult females, aged 18 years and above, who visited the various out-patient departments (OPD) of a tertiary care hospital in July 2017. A total of 640 adult females, who visited the OPDs of medicine, surgery, orthopedics and gynecology were included in this study. Data were entered and analyzed using SPSS ver 16. Chi-square test was used to test association. A p-value of less than 0.05 was considered as significant association. Results: Of the 640 participants, mostly were Hindu, aged between 20-29 years, married and had more than one child. Only, 52% females were aware of the term ‘contraception’ and 17.7% about ‘emergency contraception’. The only method of ECs they were aware of was i-pill. Commonest source of their knowledge was friends, relatives and spouse. Only 70 women knew that it can be used after unprotected intercourse and 25 knew that it can be used after failure of barrier method. Just 41.2% women used any kind of contraceptive and 5.3% women have ever used an EC. Around 28% women reported not using contraception due to lack of knowledge. Conclusions: Despite of their availability since many years, awareness about emergency contraception is low. More efforts are required to generate awareness about regular use of effective contraception and emergency contraception if required.